Enhancing Critical Thinking Skills and Science Literacy Through Stem-Based Problem Learning in Elementary School: Contributions To SDG 4 and SDG 13 - Hafifah, Dea Nur; Aulia, Ananda Mutiara (International Conference on Elementary Education, 2025)
This study was driven by the observed deficiencies in elementary students’ critical thinking skills and science literacy, which are essential foundations for advancing Sustainable Development Goal (SDG) 4 on quality education and SDG 13 on climate action. The novelty of this research resides in the contextual integration of STEM-based problem learning focused on climate change issue at the elementary school level, complemented by an integrated evaluation of 21st-century skills development and its alignment with the global Sustainable Development Goals (SDGs). Unlike previous STEM-PBL studies that primarily emphasize cognitive gains or general STEM competencies, this study uniquely embeds climate change as an authentic problem context and systematically links learning outcomes tothe SDG framework, providing a clearer pedagogical contribution and comparative advantage. The method used in this study was a quasi-experiment with a non-equivalent control group design. Thesample consisted of 62 fourth-grade elementary school students divided into two groups, an experimental group that received STEM-based problem learning and a control group that received conventional instruction. The research instruments comprised a critical thinking skills tests and a science literacy questionnaire, which had been validated by experts. The data were analyzed using inferential statistical tests, and including t-tests. The results indicated that the experimental group exposed to STEM-based problem learning experienced a statistically significant increase in critical thinking skills and science literacy compared to the control group. Students were actively engaged in all stages of the problem, ranging from design and implementation to the presentation of innovative solutions. Thefindings confirm that STEM-based problem learning is not only effective in enhancing students' cognitive and science literacy competencies but also plays a strategic role in fostering awareness of global issues, particularly climate change. Therefore, this model is proposed as an innovative pedagogical approach to advance the attainment of SDG 4 and SDG 13 within the context of elementary education. These contributions collectively position the study as a more contextually grounded and SDG-responsive extension of prior STEM-PBL research.